Penerapan Metode Diskusi Kelompok untuk Meningkatkan Minat Belajar Siswa di MI Darul Ulum Genengan - Yuana Indah Sriati; Ajeng Nurya Tri Ningsih; Vegi Teria Sofiandira; Adin Fauzi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2021)
Referring to the Instruction of the Minister of Home Affairs Number 38 of 2021 which explains, for regions that have entered levels 1 to 3 in the Covid-19 distribution map, they can open limited face-to-face learning. In response to this, many schools in Blitar Regency have implemented limited face-to-face learning, one of which is MI Darul Ulum Genengan. Besides, one of the problems that will likely occur when face-to-face learning is carried out is the lack of interest in learning when the lesson takes place. This is because students have been doing online learning at home for a long time, and when they have to return to school, there will certainly be many differences, such as the way the material is delivered and the material obtained. Therefore, the activities we carry out are aimed at helping students increase their interest in learning in class, by using the Group Discussion method. The results of this activity indicate that students are more motivated by conducting group discussions, they are more enthusiastic when studying or working with their friends, and students become more creative. It is hoped that later this activity can be followed up by teachers at MI Darul Ulum to increase interest in learning and can provide motivation during class learning.